DIGITAL DISSEMINATION COVID-19 DWIBAHASA (INDONESIA DAN BANJAR) MELALUI LITERASI SAINS VISUAL DAN MULTIMEDIA - Muhsinah Annisa; Asrani Asrani (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2020)
ABSTRACTThis community service aims to disseminate bilingual visual media related to preventing the spread of COVID-19. Besides, visual media is also expected to be able to introduce scientific literacy to the public. The service consists of two main activities, namely media dissemination through social media, such as whattsup, twitter, facebook, instagram, and virtual meetings using a video conference platform. The results of the activities were very positive from the community, where people were willing to become agents for the dissemination of bilingual visual media that had been developed as a form of COVID-19 response activities. Keyword: Billingual, Visual Media, COVID-19  ABSTRAKPengabdian ini bertujuan untuk mensosialisasikan media visual dwibahasa terkait pencegahan penyebaran COVID-19. Selain itu, media visual juga diharapkan mampu memperkenalkan literasi sains kepada masyarakat. Pengabdian terdiri dari dua kegiatan utama yaitu penyebaran media melalui sosial media seperti pada whattsup, twitter, facebook, instagram, dan pertemuan virtual menggunakan platform video conference. Hasil dari kegiatan sangat positif dari masyarakat, dimana masyarakat bersedia menjadi agen untuk penyebarluasan media visual dwibahasa yang telah dikembangkan sebagai salah satu bentuk kegiatan penanggulan COVID-19. Kata Kunci: Media Visual, Dwibahasa, COVID-19